(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Vatarakta is a disease of Avarana pathology caused by vitiated Rakta and Vata. The Vata gets vitiated by its own causes and its movement gets restricted by vitiated Rakta which leads to Vatarakta. In this disease, Vata and Rakta get vitiated by distinct etiological factors. One of the major causes of Rakta and Vata Dushti is trauma as told by Acharya Charaka in Jwar chikitsa. Severe pain is the major symptom of Vatarakta that gets relieved instantly by Raktmokshan as advised by Acharya Charak. Vedhan Karma was selected for Raktamokshan. Vedhan Karma (piercing) is one of the eight surgical procedures (Ashtavidha Shashtra Karma) explained by Acharya Sushruta. It is very simple and cost-effective. The points of Vedhan are specific according to diseases. After proper history taking and diagnosis, if Vedhankarma is done in the appropriate place we get instant results. It is safe, time-saving, and cost-effective. Hence a study was carried out using Vedhankarma in a case of painful, restricted movements of the left shoulder joint which was diagnosed as Vatarakta. For Vedhan, Suchee Shastra (26 no. needle) was used. The patient got instant relief from pain and improvement in restricted movement.